Certificate integration management platform based on identity key - Mu-zhou LIU; Jian-shu QIU; Yun-yong ZHANG; Bin-feng YAN; Si-yao ZHANG; Ya-fei TANG (Tongxin xuebao)
Asymmetric key cryptosystem plays an significant role in the field of information security.Compared with tra-ditional public key cryptosystem,the public key crypto system based on identity simplifies certificate management and reduces system communication and storage cost.A management platform and its unique merits were introduced after analyzing the current security schemes and comparing their various advantages and defects.According to the analysis of technical principles and functions,this product has a promising future.